Synthesis, characterization of vanadium oxide nanostructures and their cytotoxic activities in human cell lines - Javed Ahmad; Rizwan Wahab; Maqsood A. Siddiqui; Quaiser Saquib; Abdulaziz A. Al-Khedhairy (Journal of King Saud University: Science, 2023)
Vanadium oxide is largely applied as a chemical and industrial product in various field such as in electrochemical, photochemical and refining industries. Very limited studies are available for the use of vanadium oxide to understand the biological activity against cancer cells. The work presented here, to understand the cytotoxicity study against breast cancer cells (MCF-7). Initially, vanadium penta oxide (V2O5) nanorods were synthesized via solution process and were well characterized. The size of the crystallite, phase and morphology of the powder were scrutinized via X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) respectively. The size of each rod shaped structure is ∼2–3 µm length whereas diameter goes 200–250 nm. The cytotoxicity study with this structure has not been studied previously. Therefore, the current work carried out to investigate the efficacy against cancer cells. The cells cytotoxic assesement were analysed via MTT((3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) and NRU (Neutral Red Uptake) assays with varied V2O5 concentrations (2–200 µg/mL), which indicates the reduction in cell viability. The reactive oxygen species (ROS) were measured in cancer cells as the concentration of V2O5 increases, the ROS is increase in the cells, which is the indication of cells death. Also, the RT-PCR study revealed that the mRNA levels of apoptotic genes such as p53, bax, and caspase-3 were up regulated, whereas bcl-2, an anti-apoptotic gene, was down regulated with the interaction of V2O5 increases.